A novel DNA-binding motif in prostate tumor overexpressed-1 (PTOV1) required for the expression of ALDH1A1 and CCNG2 in cancer cells. (28th June 2019) - Maggio, Valentina; Cánovas, Verónica; Félix, Alex J.; Gómez, Valentí; de Torres, Inés; Semidey, María Eugenia; Morote, Juan; Noé, Verónique; Ciudad, Carlos J.; Paciucci, Rosanna
Abstract: PTOV1 is a transcription and translation regulator and a promoter of cancer progression. Its overexpression in prostate cancer induces transcription of drug resistance and self-renewal genes, and docetaxel resistance . Here we studied PTOV1 ability to directly activate the transcription of ALDH1A1 and CCNG2 by binding to specific promoter sequences. Chromatin immunoprecipitation and electrophoretic mobility shift assays identified a DNA-binding motif inside the PTOV-A domain with similarities to known AT-hooks that specifically interacts with ALDH1A1 and CCNG2 promoters. Mutation of this AT-hook- like sequence significantly decreased the expression of ALDH1A1 and CCNG2 promoted by PTOV1. Immunohistochemistry revealed the association of PTOV1 with mitotic chromosomes in high grade prostate, colon, bladder, and breast carcinomas. Overexpression of PTOV1, ALDH1A1, and CCNG2 significantly correlated with poor prognosis in prostate carcinomas and with shorter relapse-free survival in colon carcinoma. The previously described interaction with translation complexes and its direct binding to ALDH1A1 and CCNG2 promoters found here reveal the PTOV1 capacity to modulate the expression of critical genes at multiple levels in aggressive cancers. Remarkably, the AT-hook motifs in PTOV1 open possibilities for selective targeting its nuclear and/or cytoplasmic activities. Highlights: A novel DNA-binding motif in PTOV1 is required for ALDH1A1 and CCNG2 overexpression. PTOV1 is a direct transcriptional activator of gene expression in prostate cancer. Distinct DNA- RNA-binding motifs might direct PTOV1 nuclear and cytoplasmic actions. PTOV1, ALDH1A1, CCNG2 expression associated with prostate and colon cancer bad prognosis.